The sociogony : social facts and the ontology of objects, things, and monsters - Worrell, Mark P. (Studies in critical social sciences, 2019)
The Sociogony re-examines the social ontology of what Durkheim calls `social facts' in the light of critical and progressive hostilities to the facticity of facts and the necessity of moral absolutes in the shift from bourgeois liberalism to a neoliberal global order. The introduction offers a wide-ranging rumination on the concept of the absolute after its apparent downfall; the chapter on facts turns the problem of external authority on its head and the chapter dealing with the sociogony situates facts in a process of generation, rule, and decay. Drawing heavily on the works of Hegel, Marx, Weber, and Durkheim, the resulting synthesis is what the author refers to as a Marxheimian Social Theory that offers a new map and a stable ontology for the homeless mind.